MATLAB and Simulink Models for 'Improved State of Charge Estimation for Lithium-Sulfur Batteries' - Auger, Daniel; Propp, Karsten; Fotouhi, Abbas; Marinescu, Monica; Knap, Vaclav; Longo, Stefano (Cranfield University, 2022)
This fileset consists of Simulink models of a state estimator for lithium-sulfur batteries, as described in a research paper that has been submitted for publication.
Keywords: lithium-sulfur battery'; 'state of charge estimation'; 'extended Kalman filter'; 'online parameterzation'; 'equivalent circuit network model'; 'Electrochemistry'; 'Energy Generation; Conversion and Storage Engineering'; 'Automotive Engineering not elsewhere classified'